Progressive tauopathy disrupts breathing stability and chemoreflexes during presumptive sleep in mice - Marciante, Alexandria B.; Lurk, Carter; Mata, Luz; Lewis, Jada; Reznikov, Leah R.; Mitchell, Gordon S. (Frontiers in Physiology, 2023)
Rationale: Although sleep apnea occurs in over 50% of individuals with Alzheimer’s Disease (AD) or related tauopathies, little is known concerning the potential role of tauopathy in the pathogenesis of sleep apnea. Here, we tested the hypotheses that, during presumptive sleep, a murine model of tauopathy (rTg4510) exhibits: 1) increased breathing instability; 2) impaired chemoreflex function; and 3) exacerbation of these effects with tauopathy progression. Methods: rTg4510 mice initially develop robust tauopathy in the hippocampus and cortex, and eventually progresses to the brainstem. Type I and II post-sigh apnea, Type III (spontaneous) apnea, sigh, and hypopnea incidence were measured in young adult (5–6 months; n = 10–14/group) and aged (13–15 months; n = 22–24/group) non-transgenic (nTg), monogenic control tetracycline transactivator, and bigenic rTg4510 mice using whole-body plethysmography during presumptive sleep (i.e., eyes closed, curled/laying posture, stable breathing for >200 breaths) while breathing room air (21% O2). Peripheral and central chemoreceptor sensitivity were assessed with transient exposures (5 min) to hyperoxia (100% O2) or hypercapnia (3% and 5% CO2 in 21% O2), respectively. Results: We report significant increases in Type I, II, and III apneas (all p < 0.001), sighs (p = 0.002) and hypopneas (p < 0.001) in aged rTg4510 mice, but only Type III apneas in young adult rTg4510 mice (p < 0.001) versus age-matched nTg controls. Aged rTg4510 mice exhibited profound chemoreflex impairment versus age matched nTg and tTA mice. In rTg4510 mice, breathing frequency, tidal volume and minute ventilation were not affected by hyperoxic or hypercapnic challenges, in striking contrast to controls. Histological examination revealed hyperphosphorylated tau in brainstem regions involved in the control of breathing (e.g., pons, medullary respiratory column, retrotrapezoid nucleus) in aged rTg4510 mice. Neither breathing instability nor hyperphosphorylated tau in brainstem tissues were observed in young adult rTg4510 mice. Conclusion: Older rTg4510 mice exhibit profound impairment in the neural control of breathing, with greater breathing instability and near absence of oxygen and carbon-dioxide chemoreflexes. Breathing impairments paralleled tauopathy progression into brainstem regions that control breathing. These findings are consistent with the idea that tauopathy per se undermines chemoreflexes and promotes breathing instability during sleep.